Pemikiran Ahmad Dahlan tentang Pendidikan dan Relevansinya dengan Pendidikan Kontemporer - Nur Faizi (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2022)
This paper aims to discuss the thoughts of Ahmad Dahlan about education and its relevance to contemporary Islamic education. The research method used in this paper is qualitative library research. This research includes a biographical study because it tries to conclude, analyze and make interpretations of the characters' thoughts. The results and discussion in this paper are that Ahmad Dahlan, as a reformer of Islamic Education, answered the challenges faced by Muslims in the form of the backwardness of the education system and the stagnation of Islamic understanding. During the time of Ahmad Dahlan, the condition of Muslims began to deviate from the sanctity and purity of Islamic teachings. Ahmad Dahlan's thoughts were motivated by his concern and anxiety about the situation and condition of Muslims drowning in stagnation of thought, ignorance, and backwardness at that time. The goal of Ahmad Dahlan's thought was to cleanse Islam from the influence of wrong teachings (heresy, superstition, and superstition), reform the Islamic education system, and improve the social life of Muslims. The relevance of Ahmad Dahlan in Islamic education today can be seen from the aspect of the goals of Islamic education. Keywords: Ahmad Dahlan, Education, religious, conservative Tulisan ini bertujuan untuk membahas pemikiran Ahmad Dahlan tentang pendidikan dan relevansinya dengan pendidikan Islam kontemporer. Metode penelitian yang digunakan dalam makalah ini adalah penelitian kepustakaan yang bersifat kualitatif. Penelitian ini termasuk penelitian biografi, karena mencoba menyimpulkan, menganalisis dan membuat interpretasi dari pemikiran para tokoh. Hasil dan pembahasan dalam tulisan ini adalah Ahmad Dahlan sebagai seorang pembaharu Pendidikan Islam menjawab tantangan yang dihadapi umat Islam berupa keterbelakangan sistem pendidikan dan stagnasi pemahaman Islam. Pada masa Ahmad Dahlan, kondisi umat Islam mulai menyimpang dari kesucian dan kemurnian ajaran Islam. Pemikiran Ahmad Dahlan dilatarbelakangi oleh keprihatinan dan kegelisahannya terhadap situasi dan kondisi umat Islam yang saat itu sedang tenggelam dalam stagnasi pemikiran, kebodohan dan keterbelakangan. Tujuan pemikiran Ahmad Dahlan adalah membersihkan Islam dari pengaruh ajaran sesat (bid'ah, tahayul dan tahayul), mereformasi sistem pendidikan Islam dan memperbaiki kehidupan sosial umat Islam. Relevansi Ahmad Dahlan dalam pendidikan Islam saat ini dapat dilihat dari aspek tujuan pendidikan Islam.